Optimization of Vehicle Volume for Multi Lane Free Flow-Based Contactless Transaction System - Ramadhani Puspa Pratami Putri; Bambang Syairudin (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study evaluates the effectiveness of the tapping transaction system using e-toll at the Sidoarjo 2 Toll Gate and analyzes the potential for optimizing vehicle volume through the implementation of a contactless transaction system based on Multi-Lane Free Flow (MLFF). The research method used is quantitative descriptive, with primary data obtained through interviews and observations, and secondary data from government and company documents. Data analysis was carried out using SPSS 26 with the Chi-Square test to determine system stability based on arrival time, service level, and waiting time. The results showed that the highest vehicle arrival rate occurred on Monday, with peak traffic reaching 1,816 vehicles/hour. Although the current system is still optimal under normal conditions, the increase in vehicle volume during long holidays requires additional toll booths. Implementation of MLFF, with transaction times approaching zero, can eliminate queues and significantly improve traffic flow efficiency. This study emphasizes the importance of implementing MLFF at toll gates with high vehicle volumes and recommends further studies on aspects of technology, cost, and risk to ensure a smooth transition. The implementation of MLFF is a crucial step in maintaining long-term operational efficiency and improving toll road performance.